ANALYZING THE LIFESTYLE BEHAVIOUR ON MOVIE THEATER CONSUMERS AT UNIVERSITY STUDENTS IN MANADO - Muin, Resti C; Pangemanan, Sifrid S.; Tielung, Maria V.J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Lifestyle behaviour also the activity of people that has been doing repeatedly by the people and it can be changing depend to the lifestyle and sometimes it may become peopleâ€™s habit. It also can affect by the social activity or by the environment that affect the people. The aim of this study is to analyze how is lifestyle behaviour of movie theater consumer as college student and what are the factors that effect lifestyle behaviour and the objectives is to know how is the lifestyle behaviour on movie theater consumer and what factors that effect lifestyle behaviour. In order to achieve these objectives the researcher got information from 15 informants using qualitative study which is in-depth interview and uses purposive sampling and snowball sampling. The results showed that Lifestyle Behaviours on Movie Theater Consumer of University student is a Lifestyle that very common, very interesting, modern, and positive, this kind of lifestyle of watching movies in Cinema has come naturally, and the university students that part with this research are very happy with the existence of the movie theater or the Cinema, through the development tehnology in this era, it leads people especially university student to come to Cinema for watching movie, The recomendation For the Cinema, it is more better to keep improving the service and always provide a good movie that could educate all the univesrsity students.Â Keywords: lifestyle behaviour, movie theater consumers